2017
DOI: 10.1051/0004-6361/201730980
|View full text |Cite
|
Sign up to set email alerts
|

A new study of the chemical structure of the Horsehead nebula: the influence of grain-surface chemistry

Abstract: A wide variety of molecules have recently been detected in the Horsehead nebula photodissociation region (PDR) suggesting that: (i) gas-phase and grain chemistries should both contribute to the formation of organic molecules, and (ii) far-ultraviolet (FUV) photodesorption may explain the release into the gas phase of grain surface species. In order to tackle these specific problems and more generally in order to better constrain the chemical structure of these types of environments we present a study of the Ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Current pure gas-phase models cannot reproduce the inferred H 2 CO, CH 3 OH and COMs abundances in the Horse-head PDR (Guzmán et al 2011, 2013), which supports the grain surface origin of these molecules. Le Gal et al (2017) was able to reproduce the observed COMs abundances using a chemical model with grain surface chemistry and found that chemical desorption, instead of photodesorption, is the main process to release COMs to the gas phase. CH 3 CN and CH 3 NC, key species for the formation of prebiotic molecules, seem to have a very specific formation pathway in the PDR (Gratier et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Current pure gas-phase models cannot reproduce the inferred H 2 CO, CH 3 OH and COMs abundances in the Horse-head PDR (Guzmán et al 2011, 2013), which supports the grain surface origin of these molecules. Le Gal et al (2017) was able to reproduce the observed COMs abundances using a chemical model with grain surface chemistry and found that chemical desorption, instead of photodesorption, is the main process to release COMs to the gas phase. CH 3 CN and CH 3 NC, key species for the formation of prebiotic molecules, seem to have a very specific formation pathway in the PDR (Gratier et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rubin et al (1971);Cazaux et al Kahane et al (2013); Mendoza et al (2014); López-Sepulcre et al (2015); Belloche et al (2017); Ligterink et al (2017); McGuire et al (2018)), in the circumstellar envelopes of AGB stars (Cernicharo et al (2000)), shocked regions (Arce et al (2008); Codella et al (2017); Lefloch et al (2017)) and even in external galaxies (Muller et al (2013)). Despite their presence has been known for decades, how iCOMs are synthesized is still an open question and under debate (Herbst & van Dishoeck (2009) ;Caselli & Ceccarelli (2012); Woods et al (2013); Balucani et al (2015); Butscher et al (2017); Butscher et al (2019); Fedoseev et al (2015); Enrique-Romero et al (2016); Enrique-Romero et al (2019); Gal et al (2017); Rivilla et al (2017); Vasyunin et al (2017); Rimola et al (2018); Lamberts et al (2019)). Two different paradigms have been proposed: i) on the surfaces of grains (either during the cold prestellar or warmer collapse phase (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its low ionization potential, sulfur is expected to be ionized up to A v ~ 7 mag (see e.g. Le Gal et al 2017) and is a plausible precursor of NS + . The abundance of the ion H 2 S + , formed by the reaction S+H3+, might be important in deeper layers of the molecular cloud depending on the cosmic ray ionization rate (Sternberg & Dalgarno 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Dust grain temperatures in this low-UV PDR are ~20-30 K, lower than the evaporation temperature of H 2 S, the main sulphur reservoir in solid state. In the gas phase, S and S + are expected to be the main sulphur reservoirs (Le Gal et al 2017; Goicoechea et al 2006). Unfortunately the observation of these species is not easy in the (sub-)millimeter wavelength range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation